2018
DOI: 10.1103/physreva.98.063819
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional carrier-envelope-phase map of focused few-cycle pulsed Gaussian beams

Abstract: We derive an analytical expression that describes the complete three-dimensional carrier-envelope phase (CEP) distribution of in the focal volume of ultrashort pulsed Gaussian beams focused by spherical mirrors or lenses. The focal CEP map depends on the so-called factor g specifying the frequency-dependence of the beam width of the source few-cycle pulse, on its chirp and on the small chromatic aberration introduced by a lens without appreciably distorting or broadening the few-cycle pulse. We show how to tai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The spatial ΔCEP( x , y , z ) distribution of a short, broad-spectrum beam can acquire various shapes as measured in earlier studies 25 , 26 , 35 , and supported by theoretical studies 26 , 45 47 . In Fig.…”
Section: Resultssupporting
confidence: 59%
“…The spatial ΔCEP( x , y , z ) distribution of a short, broad-spectrum beam can acquire various shapes as measured in earlier studies 25 , 26 , 35 , and supported by theoretical studies 26 , 45 47 . In Fig.…”
Section: Resultssupporting
confidence: 59%
“…. Complete descriptions of the phase at arbitrary longitudinal and transverse locations throughout the focal volume have been derived for linearly polarized light [16,23,24], but we will consider rather the longitudinal field produced from focusing radially-polarized Gaussian light fields for the acceleration application.…”
Section: (B))mentioning
confidence: 99%
“…(1) and ( 2) and r max = 0] only introduces minor changes on the pulse temporal shape [Figs. 2(a), (b) and (c)], irrespective of the particular value of g 0 , i. e., the pulse continues to be an approximately single-cycle, Gaussianlike pulse during the whole propagation [42], with slightly blue shifted frequency for g 0 > 0, and red shifted frequency for g 0 < 0 about the focus [38,39,44], and with different maps of carrier-envelope phase in the focal vol-ume, as studied in detail in [44,48].…”
Section: B Previous Results and Open Problemsmentioning
confidence: 99%
“…Fortunately, for pulses with at least one carrier oscillation, it has been theoretically suggested and experimentally demonstrated that it is only the variation of the Rayleigh distance with frequency in the vicinity of the carrier frequency ω 0 that determines most of propagation properties of pulsed beams [44,46,48]. The different situations are suitably described by a single dimensionless parameter called the g 0 -factor defined as [44]…”
Section: Preliminaries On Ultrafast Laguerre-gauss Vorticesmentioning
confidence: 99%
See 1 more Smart Citation